2019
DOI: 10.1101/773481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alcohol Drinking Alters Stress Coping via Extended Amygdala Kappa Opioid Receptor Signaling in Male Mice

Abstract: Maladaptive responses to stress are a hallmark of alcohol use disorder, but the mechanisms that underlie this are not well characterized. Here we show that kappa opioid receptor (KOR) signaling in the bed nucleus of the stria terminalis (BNST) is a critical molecular substrate promoting a maladaptive behavioral phenotype following heavy alcohol drinking.Altered responses to an innate stressor were associated with enhanced PFC-driven excitation of prodynorphin-containing neurons in the BNST during protracted wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In this line, a recent report in male C57BL/6J mice exposed to a daily "binge-like" vapor exposure shows a lasting increase in impulsive-like behavior in the 5choice serial reaction time task (Starski, et al 2020). Also reminiscent of behavioral disinhibition, recent studies in male mice drinking in the IAA model showed increased aggressivity (Hwa, et al 2015) a maladaptive response to a predator odor in IAA drinking mice (Hwa, et al 2019). Albeit hard to interpret, the higher average velocity observed in male drinkers compared to water drinking controls on the EZM in our study could hint at a subtle effect of alcohol that affects male and female mice differently.…”
Section: Discussionmentioning
confidence: 94%
“…In this line, a recent report in male C57BL/6J mice exposed to a daily "binge-like" vapor exposure shows a lasting increase in impulsive-like behavior in the 5choice serial reaction time task (Starski, et al 2020). Also reminiscent of behavioral disinhibition, recent studies in male mice drinking in the IAA model showed increased aggressivity (Hwa, et al 2015) a maladaptive response to a predator odor in IAA drinking mice (Hwa, et al 2019). Albeit hard to interpret, the higher average velocity observed in male drinkers compared to water drinking controls on the EZM in our study could hint at a subtle effect of alcohol that affects male and female mice differently.…”
Section: Discussionmentioning
confidence: 94%